The Requirements Analysis of Satellite Application in Marine Transportation Industry - Zhen LI; Yumin ZHAO; Guangyue XUE; Yunfei AI; Falong LIU (天地一体化信息网络)
With the rapid development of modern technologies and satellite communication, the need to apply satellite communication in the transport field in China has become stronger and stronger.The development and application status of the major satellite communication systems in China and abroad was introduced, and nine major application services of traff c navigation monitor at sea, emergency communications, broadband access of ship etc were studied, and the application of maritime satellite communications and the development tendency were explored, took into account the status and existing problems of maritime satellite communications in China.Based on the above, recommendations on the construction of an independent and controllable space-terrestrial integrated satellite communication network in China for maritime applications were provided.